New technologies and industrialization prospects of developing countries - Wilfried Lütkenhorst (Intereconomics, 1989)
Industrial technologies are both an outcome of the industrialization process and one of its main driving forces. The introduction of new technologies can be seen as one of several important factors which directly and indirectly change the context and modes of international industrial production, thus being among the key determinants of the international division of labour. Given the accelerating pace of technological development in industry, there is an urgent need not only to identify incipient technological breakthroughs but above all, at an early stage, to analyze their short-and long-term implications for the worldwide industrialization process and to reassess the validity of crucial assumptions underlying developing countries' current industrial strategies.
Keywords: 330; Industrialization